2022
DOI: 10.1177/0271678x221142139
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic evaluation and assessment of longitudinal changes in reference region and extracerebral [18F]MK-6240 PET uptake

Abstract: [18F]MK-6240 meningeal/extracerebral off-target binding may impact tau quantification. We examined the kinetics and longitudinal changes of extracerebral and reference regions. [18F]MK-6240 PET was performed in 24 cognitively-normal and eight cognitively-impaired subjects, with arterial samples in 13 subjects. Follow-up scans at 6.1 ± 0.5 (n = 25) and 13.3 ± 0.9 (n = 16) months were acquired. Extracerebral and reference region (cerebellar gray matter (CerGM)-based, cerebral white matter (WM), pons) uptake were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…The pattern of [ 18 F]MK-6240 uptake distribution was consistent with previous studies 17,23,69,70 and with the expected localization of tau across the AD spectrum 20,71,72 , and was similar in the Test and Retest scans. Some degree of meningeal or extracerebral signal was observed in all subjects, with 7 of them presenting visually high extracerebral signal.…”
Section: Brain Distribution: Visual Inspectionsupporting
confidence: 89%
See 2 more Smart Citations
“…The pattern of [ 18 F]MK-6240 uptake distribution was consistent with previous studies 17,23,69,70 and with the expected localization of tau across the AD spectrum 20,71,72 , and was similar in the Test and Retest scans. Some degree of meningeal or extracerebral signal was observed in all subjects, with 7 of them presenting visually high extracerebral signal.…”
Section: Brain Distribution: Visual Inspectionsupporting
confidence: 89%
“…Currently, there is no consensus on the optimal reference region for [ 18 F]MK-6240, and various studies have chosen different regions for normalization 17,19,23,[27][28][29][30][31][32] . In a recent study, Fu et al 23 evaluated longitudinal changes in reference region SUV 90 − 110 , as well as the impact of the reference region on target region outcomes. The authors suggested that, for cross-sectional studies, eroded CerGM may be preferred for differentiation between CN and AD groups, whilst eroded WM or pons may be preferred for detecting longitudinal [ 18 F]MK-6240 changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…that different off‐target binding adjustment methods, including PVC and erosion, 38 did not significantly impact relationships between measured uptake and other endpoints. It can be noted that different compensation methods have various advantages and disadvantages when applied to longitudinal evaluation (such as increased variability with PVC), 39 but this was not the focus or scope of the present work. The finding of general concordance between visual detection of uptake and quantitative values for [ 18 F]MK‐6250 was consistent with results reported by others 34,40 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, eroded WM may be more sensitive for longitudinal analyses. An eroded subcortical WM or eroded subcortical WM cerebellar composite RR may be more suitable for longitudinal analyses examining regional patterns of change [157][158][159][160]. The eroded WM RR more consistently detected significant change over time [157].…”
Section: Region Selection For Determining Tau Pet Positivitymentioning
confidence: 99%